V–Ti-Based Solid Solution Alloys for Solid-State Hydrogen Storage - Shaoyang Shen; Yongan Li; Liuzhang Ouyang; Lan Zhang; Min Zhu; Zongwen Liu (Nano-Micro Letters)
Highlights Hydrogen storage performance of V-Ti-based solid solution alloys is related to the elementary composition, phase structure, and homogeneity. Micro-strain accumulation is responsible for capacity degradation. Low-cost and high-performance V-Ti-based solid solution alloys with high reversible hydrogen storage capacity, good cyclic durability, and excellent activation performance should be developed.